On ‘‘investment decisions in the theory of finance: Some antinomies and inconsistencies’’ - DE REYCK, Bert (Institutional Knowledge at Singapore Management University, 2005)
In the paper “Investment Decisions in the Theory of Finance: Some antinomies and inconsistencies”, Magni [Eur. J. Operat. Res. 137 (2002) 206] shows that using the net present value rule for making investment decisions can lead to inconsistencies and antinomies. The author claims that the so-called equivalent-risk tenet of finance, whereby an investor needs to compare an investment opportunity with an asset of equivalent risk, is impossible to implement. In this paper, we show that the main thesis of this paper is incorrect, and that finance theory, when applied correctly, can be used to value investment projects by comparing assets of equivalent risk. We point out the fallacies in the author's reasoning and provide an alternative, and correct, methodology for valuing the projects described in the paper.